New Forms of Democracy - Hans Gersbach (Center for Economic Studies and ifo Institute (CESifo), 2022)
In the third decade of the 21st century, digitization, global events, challenges from authoritarian states, and difficulties of particular democracies to function properly confront democracy with a new series of challenges and opportunities that will force it to reinvent itself. The last decades have produced an accelerating flow of ideas for new forms of democracy. We survey a long period in the quest for such new forms and point to next inventions for such forms. We suggest to experiment with new ways for democracy to extend the choice of democratic processes that can be implemented in real-life situations, with the beneficial side-effect that democracy might remain the only sustainable structure for self-governing societies.
Keywords: D02; D70; D82; D83; 330; democracy; new forms; voting; elections; social innovations; public policy